Digestible lysine levels in semi-heavy laying hens in the period from 28 to 44 weeks of age - Santos, Tiago Antônio dos; Geraldo, Adriano; Machado, Luiz Carlos; Gonçalves, Rogério Amaro; Pelícia, Kléber; Simão, Sérgio Domingos (Acta Scientiarum. Animal Sciences, 2014)
This study aimed to evaluate the performance of laying hens subjected to heavy semi-low crude protein (14.0%) and lysine levels while maintaining the same relation of digestible amino acid/ digestible lysine. A commercial line of 420 Isa Brown laying hens, in the period from 28 to 44 weeks of age, were distributed in 42 experimental plots. A completely randomized design with six treatments and seven replicates in four periods of 28 days/each was used. The treatments were: Control - Formulated according to the nutritional requirements proposed in the strain, containing 16.92% crude protein, 0.750% digestible lysine. Treatments 1 to 5, with crude protein levels of 14% and 0.600% of digestible lysine, 0.675%, 0.750%, 0.825% and 0.900%, respectively. The requirement of lysine, in relation to other digestible amino acids, can be estimated at 0.750% in diet with 14% crude protein, which corresponds to the average daily intake of 876 mg lysine dig. hen-1 day-1, without compromising the performance of hens.